1995
DOI: 10.1016/s0022-5223(95)70007-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies of hypoxemic/reoxygenation injury: Without aortic clamping

Abstract: This study tests the hypothesis that antioxidants administered before reoxygenation can reduce oxygen-mediated damage and improve myocardial performance. Of 25 Duroc-Yorkshire piglets (2 to 3 weeks, 3 to 5 kg) five underwent 60 minutes of cardiopulmonary bypass without hypoxemia (control group), and five others underwent 30 minutes of hypoxemia on cardiopulmonary bypass with a circuit primed with oxygen tension about 25 mm Hg blood followed by reoxygenation on cardiopulmonary bypass (no treatment). In vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Catalase is a potential enzyme with the highest turnover rate among antioxidant enzymes [64]. It is used as an effective and relevant antioxidant therapy, particularly when the cells need support during ischemic conditions [65][66][67][68][69]. This study showed that delivery of exogenous catalase to the target site, timely and effectively, appeared to prevent cell/tissue from ischemia and promised support for tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase is a potential enzyme with the highest turnover rate among antioxidant enzymes [64]. It is used as an effective and relevant antioxidant therapy, particularly when the cells need support during ischemic conditions [65][66][67][68][69]. This study showed that delivery of exogenous catalase to the target site, timely and effectively, appeared to prevent cell/tissue from ischemia and promised support for tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…A N2-Mercaptopropionilglicina (N2-MPG), potente tiol inibidor da síntese de radicais superóxidos, tem sido testada como terapêutica adjuvante dos processos de isquemia/reperfusão em diversos órgãos, como fígado 11 , pâncreas 12 , pulmão 13 , e principalmente no coração 14,15,16,17,18 freqüentemente acometido por tal processo.…”
Section: Introductionunclassified